A multi-modal approach for evaluating player experience on different gaming platforms. (9th March 2020) - Aker, Çakır; Inal, Yavuz; Rızvanoğlu, Kerem
The aim of this experimental study was to adopt a multi-modal approach to analyse player experience on PC and mobile gaming platforms, and identify both the factors that potentially have an effect on this experience and the set of methods that are effective on measuring it. Game experience questionnaire was enriched through usability scales, semi-structured interviews and player observations. Data was collected from 20 undergraduate university students that were selected from casual gamers that had never played the Plants vs. Zombies game before. Results of the study showed that participants who played on the PC platform declared more positive feelings when compared to the players of the mobile platform. The bivariate correlations between the game experience items on each platform showed that flow, competence, and challenge were the marker components of game experience that differed due to the players' game experience on each platform.